Dietary inflammation score is associated with perceived stress, depression, and cardiometabolic health risk factors among a young adult cohort of women. (October 2022) - Knight, Rachel; Cedillo, Yenni; Judd, Suzanne; Tison, Stephanie; Baker, Elizabeth; Moellering, Douglas
Summary: Background and aims: One of the most pressing issues in the field of cardiometabolic disease is the growing co-occurrence of poor mental health. A whole foods-based, hypothesis-driven dietary inflammation score (DIS) was created to better understand the association between dietary patterns, inflammation, and physiological health. However, this diet quality scoring method has not been observed in young adults, nor has its association with mental health been observed. This study 1) examined differences in cardiometabolic health measures by dietary inflammation score (DIS) tertiles and 2) examined the association between DIS and psychosocial stress variables, perceived stress, and depression. Methods: Psychosocial and food frequency questionnaires, demographics, anthropometrics, and clinical measures were collected from sixty-two metabolically healthy African American and European American females, ages 18–45, from 2014 to 2016 in Birmingham, AL. Analysis of Variance was used to observe differences in all cardiometabolic variables by DIS tertile. Linear regression was used to observe the relationship between independent, continuous variable DIS and dependent variables, depression, and perceived stress. Results: There were significant differences between DIS tertiles for cardiometabolic and psychosocial stress measures. DIS was significantly positively associated with depression after controlling for body fat percentage (P = 0.003) and education, income, and race (P = 0.01). DIS was significantly associated with perceived stress after controlling for body fat percentage (P = 0.0004), and education, income, and race (P = 0.0005). Conclusion: This study is significant for its contribution in understanding how cardiometabolic health differs by DIS tertile, and how dietary inflammation scores are associated with depression and perceived stress among young adult women. Highlights: Inflammation is an important marker of health and is intricately linked to nutrition. Dietary inflammation is associated with high weight status, poor cardiovascular health, and psychosocial outcomes. DIS is positively associated with depression and perceived stress after, controlling for obesity and covariates. Nutrition research should continue exploring the role of food in eliciting the inflammatory response.